Critical speed as a predictor of aerobic performance in children - Wagner de Campos; Rodrigo Bozza; Anderson Zampier Ulbrich; Antonio Stabelini Neto; Italo Quenni Araujo de Vasconcelos; Luís Paulo Gomes Mascarenhas (Universidade Federal de Santa Catarina, 2007)
To compare times achieved in a 1,600m rural road run with the times predicted from critical speed, in additionto verify any association between critical speed and VO2max with the aerobic performance (1,600m time) of children. The sample consisted of 25 boys and 39 girls, aged 9 to 11 years. Their critical speeds were determined using the work versus time model, performed in the 200m and 800m maximum runs. The value of VO2max was measured using a 20-meter shuttlerun test. Endurance performance was determinate from the time obtained in a rural 1,600m road run. Statistical proceduresused were descriptive analyses, Student's t test and Pearson's moment correlation, with signifi cance level set at p<0.05. The times achieved for aerobic performance were significantly lower than the performance predicted from critical speed, forboth sexes (males: 8.43 ± 0.78 min versus 10.16 ± 1.37 min; females: 9.09 ± 0.75 min versus 10.30 ± 1.09 min) (p=0.0001). Significant inverse relationships were observed between critical speed and aerobic performance for both subsets (males:r= -0.52; females: r= -0.70), and between VO2max and aerobic performance in the case of females (r= -0.48). In this study critical speed was not shown to be a predictor of performance in a 1,600m road run. However, the significant correlationsobserved suggest that critical speed could be used as a tool to control endurance training in children. RESUMO O estudo teve como objetivo comparar o tempo obtido na prova de 1.600m com o tempo predito pela velocidade crítica, bem como verifi car a associação da velocidade crítica e da potência aeróbia (VO2máx) com o desempenho aeróbio (tempo 1.600m) em crianças. A amostra foi composta de 25 meninos e 39 meninas, com faixa etária entre 9 a 11 anos, classifi cadas nos estágios de maturação sexual 1 e 2 de Tanner. A velocidade crítica foi obtida pelo modelo de avaliação trabalho versus tempo, na realização de dois tiros máximos de 200m e 800m. O VO2máx foi obtido através do teste de vai-vem de 20m. O desempenho aeróbio foi obtido através do tempo de percurso em uma prova rústica de 1.600m. Utilizou-se a estatística descritiva, teste "t" student e a correlação de Pearson, adotando p<0,05. Em ambos os grupos, odesempenho obtido na prova de 1.600m foi significativamente menor que o desempenho predito pela velocidade crítica (masculino: 8,43 ± 0,78 min versus 10,16 ± 1,37 min; feminino: 9,09 ± 0,75 min versus 10,30 ± 1,09 min) (p= 0,0001).Observaram-se correlações inversamente significativas entre a velocidade crítica e o desempenho aeróbio nos grupos masculino e feminino (r= -0,52 e r= -0,70, respectivamente), e entre o VO2máx e o desempenho aeróbio no grupo feminino(r= -0,48). Para este estudo, a velocidade crítica não se apresentou como preditor para prova de 1.600m. No entanto, as correlações significativas indicam que a velocidade crítica pode ser utilizada como ferramenta para controle de treinamentoaeróbio em crianças.